UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK MELALUI METODE PEMBELAJARAN ACTIVE LEARNING TIPE CARD SORT PADA MUATAN IPAS DI KELAS IV SEKOLAH DASAR - Cici Adila Fiaski; Eka Sastrawati; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how the use of the card sort type of active learning method can increase student learning activity in grade IV at SDN 182/I Hutan Lindung. This study was conducted at SDN 182/I Hutan Lindung during the 2024/2025 academic year. This research used Classroom Action Research (CAR) consisting of two cycles, where the data collected were in the form of observational data through observation sheets of students' social skills and also observations of teachers using the card sort learning model. This research was conducted in 4 stages, namely planning, implementation, observation, and reflection. The results of this study show an increase in student learning activity in the IPAS subject using the Active Learning model of the Card Sort type, as seen in the table of increased. learning activity among fourth-grade students at SDN 182/1 Hutan Lindung. at SDN 182/1 Hutan Lindung. In the pre-intervention phase, the percentage was 44.41% with a D rating (Poor), increasing in cycle I by 19.24% or obtaining a percentage of 63.65% with a C rating (Fair), and increasing again in cycle II by 21.38% or obtained a percentage of 85.03% with a grade of A (Very Good) and has met the predetermined success criteria of 70%. Therefore, it can be concluded that the application of the Active Learning method of the Card Sort type in IPAS learning in fourth grade elementary school can increase student learning activity. From the results of this study, it is recommended that teachers continue to improve their competence and knowledge regarding various ways to increase learning activity, one of which is the application of the Card Sort type of Active Learning method in IPAS learning to increase student learning activity in elementary schools.